Local Wisdom: A Lesson Learned in Village Governance - Putu Prema Sulistyaning Putri; Christian Alessandro Noreen; Aprina Nugrahesthy Sulistya Hapsari (Yayasan Rumah Peneleh, 2022)
This research aims to explore the role of local wisdom to drive whistleblowing systems for an accountable and transparent financial system in Tanjungsari village, Boyolali district. Qualitative descriptive method through in-depth interviews and documentation with the research stages covering data reduction, data triangulation, data presentation, and conclusion was employed. The results show that the role of local wisdom in Tanjungsari village is interpreted in terms of being able to hold the implementation of whistleblowing, so it can cause a decrease in the quality of the information provided to stakeholders as a form of accountability and transparency in its efforts to realize good governance. Data collection in this study was limited by a lack of public interest and was therefore limited to certain sources. This research is expected to provide practical benefits to the public and the Tanjungsari Village government as well as the central government to evaluate and follow up on the impact of the value of local wisdom on the Tanjungsari village community's intention to carry out whistleblowing to support better public sector accounting governance.